Operations risk managing a key component of operations risk under Basel II - Loader, David
Operations Risk--a form of Operational Risk, is becoming increasingly important as more and more sophisticated products and the use of those products occurs in the financial services industry. Outsourcing, including overseas outsourcing, is changing the structure of firms and particularly operations teams. Thus understanding the existing and the changing risk environment in operations functions and its impact on operational risk is centrally important today. The book focuses on areas such as technology risk, people risk, and settlement risk, examining the dangers that lurk within different organisations. Case studies throughout the book illustrate the way in which risk can become magnified and ultimately become a serious danger to the businesses concerned. The reader is challenged throughout the book to interpret given situations in Operations Risk so as to understand the impact of the risks and devise solutions through a series of exercises included in the relevant chapters. (answers are provided). This self-test approach will help reinforce understanding of the detailed material contained throughout the book. *Offers the knowledge, tools, techniques, and solutions necessary to recognize and evaluate operations risk *Concise, easy to read format provides practical solutions and techniques that readers can implement tomorrow *Case studies and "self-test" features ensure practical understanding.